Advances in the Role of Dark Septate Endophytes in the Plant Resistance to Abiotic and Biotic Stresses - Mila Santos (MDPI AG, 2021)
Endophytic fungi have been studied in recent decades to understand how they interact with their hosts, the types of relationships they establish, and the potential effects of this interaction. Dark septate endophytes (DSE) are isolated from healthy plants and form melanised structures in the roots, including inter- and intracellular hyphae and microsclerotia, causing low host specificity and covering a wide geographic range. Many studies have revealed beneficial relationships between DSE and their hosts, such as enhanced plant growth, nutrient uptake, and resistance to biotic and abiotic stress. Furthermore, in recent decades, studies have revealed the ability of DSE to mitigate the negative effects of crop diseases, thereby highlighting DSE as potential biocontrol agents of plant diseases (BCAs). Given the importance of these fungi in nature, this article is a review of the role of DSE as BCAs. The findings of increasing numbers of studies on these fungi and their relationships with their plant hosts are also discussed to enable their use as a tool for the integrated management of crop diseases and pests.